Detecting left ventricular impaired relaxation in cardiac MRI using moving mesh correspondences. Issue 124 (February 2016) - Punithakumar, Kumaradevan; Ben Ayed, Ismail; Afshin, Mariam; Goela, Aashish; Islam, Ali; Li, Shuo; Boulanger, Pierre; Becher, Harald; Noga, Michelle
Abstract : Highlights: A semi-automatic method was proposed to assess the cardiac LV diastolic function. A non-rigid registration was applied to track the endocardial boundary points. LV volume and filling rates are computed over the entire cardiac cycle. The peaks of early and late ventricular filling waves were detected automatically. Experimental evaluations were performed over CMR and echo datasets from 47 subjects. Abstract: Anatomical cine cardiovascular magnetic resonance (CMR) imaging is widely used to assess the systolic cardiac function because of its high soft tissue contrast. Assessment of diastolic LV function has not regularly been performed due the complex and time consuming procedures. This study presents a semi-automated assessment of the left ventricular (LV) diastolic function using anatomical short-axis cine CMR images. The proposed method is based on three main steps: (1) non-rigid registration, which yields a sequence of endocardial boundary points over the cardiac cycle based on a user-provided contour on the first frame; (2) LV volume and filling rate computations over the cardiac cycle; and (3) automated detection of the peak values of early ( E ) and late ventricular ( A ) filling waves. In 47 patients cine CMR imaging and Doppler-echocardiographic imaging were performed. CMR measurements of peak values of the E and A waves as well as the deceleration time were compared with the corresponding values obtained in Doppler-Echocardiography. For the E / A ratio the proposed algorithm for CMR yielded a Cohen's kappa measure of 0.70 and a Gwet's AC1 coefficient of 0.70. Conclusion: Semi-automated assessment of the left ventricular (LV) diastolic function using anatomical short-axis cine CMR images provides mitral inflow measurements comparable to Doppler-Echocardiography.